Development of Formative Assessment Based on Wordwall Games on the Material of Atomic Theory - Sari, Jossy Marinda; Hairida*, Hairida; Enawaty, Eny; Erlina, Erlina; Sahputra, Rachmat; Afriyanti, Fitria (Jurnal Pendidikan Sains Indonesia, 2025)
The implementation of formative assessment in chemistry learning remains suboptimal, as many teachers still rely on conventional methods and rarely utilize innovative digital media such as educational games. This study aims to determine the level of validity and response from chemistry teachers and students to formative assessment media based on wordwall games on the material of the development of atomic theory. The research method used is research and development with the ADDIE model which consists of analysis, design, development, implementation and evaluation stages but this research only reaches the development stage. The data collection techniques used are direct communication techniques with interviews and indirect communication by providing media validation sheets and questions and response questionnaires for chemistry teachers and students. The results of validation by experts on the question aspect obtained a percentage of 91.67% and on the media aspect of 95%, both of these aspects fall into the category of very feasible. The average percentage of chemistry teachers' response to formative assessment media based on wordwall games on the material of the development of atomic theory is 88.3%. While the average response of students to the product obtained a percentage of 82.67% with a very attractive category. Based on the results of validation and response tests, it can be concluded that the wordwall games-based formative assessment product on the material of the development of atomic theory is feasible to use in supporting the implementation of formative assessmentsinlearning